Life Situations and Institutional Supports of Women University Students with Family and Job Responsibilities - Alice Home; Cora Hinds (Adult Education Research Conference, 2000)
This empirical study focuses on Canadian women studying adult education, social work, and nursing, while managing paid work and family roles. Qualitative data illustrate survey findings on the contribution of life situations and institutional supports to role strain and stress experienced by these non-traditional university students.